Hubungan antara durasi tidur dan kualitas hidup dengan kegemukan pada mahasiswa keperawatan UMP - Cindy Yuni Fitri; Supriyadi Supriyadi (Jurnal Keperawatan Abdurrab, 2021)
ABSTRACT Background : Overweight and obesity is a common health problem and continues to increase at this time.Overweight and obesity can affect both all ages ranging from children, adolescents, to the elderly, and all genders, either male or women. Factors that influenced obesity including genetic, physical activity, and eating patterns. In addition, quality of life and duration of sleep were among the factors that affected obesity. Less sleeping at night was related to the occurrence of overweight. The occurrence of overweight became higher whena person slept with a duration of 7 hours per day. This showed that the less time to sleep the greater the occurrence of overweight. While the quality of one's life was related to unhealthy lifestyles such as the habits of having dinner and snacks at night, the habit of eating high-fat fast food, and rarely exercising.Objective: To determine the correlation between sleep duration and quality of life with obesity in Nursing students of Universitas Muhammadiyah Purwokerto.Method: Observational analytic with cross sectional approach was used in this study. The samples were taken by using random sampling technique. There were 30 respondents who fit the inclusion and exclusion criteria.Univariate and bivariate with chi square test were used to analyzed the data.Results: (1)There was a correlation between sleep duration and obesity in Nursing students with a value = 0.025.(2) There was no relationship between quality of life and obesity in Nursing students with a value = 0.855. Conclusions: Lack of sleeping can affect the occurrence of overweight to someone but there is no effect on the quality of life to overweight. Keywords: Sleep duration, quality of life, overweight, students.